What does sound look like? Musical iconography in the quilts of Castelo Branco - Castilho, M.L.C. (2024)
Castelo Branco embroidery, which is closely linked to quilts, has become the “ex-libris” of the city and one of the most important aspects of its cultural identity and heritage. A rich variety of motifs are embroidered in natural silk on linen, using an established design as a guide. This article aims to analyze and characterize the motifs that suggest sound — the sounds of animals, the environment, and musical instruments.